2022
DOI: 10.1136/bmjqs-2021-014095
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating patient-reported outcome measures in Peru: a cross-sectional study of satisfaction and net promoter score using the 2016 EnSuSalud survey

Abstract: BackgroundPatient-reported measures attempt to quantify the value health services provide to users. Satisfaction is a common summative measure, but often has limited utility in identifying poor quality care. We compared satisfaction and the net promoter score (NPS), which was developed to help businesses quantify consumer sentiment, in a nationally representative survey in Peru. We aimed to compare NPS and satisfaction as individual ratings of care, assess the relationship of patient-reported experience rating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In addition to its relationship to visit quality, facility recommendation score might be less cognitively demanding for respondents and produces a continuous response that requires fewer assumptions in analysis than other measures, such as Likert scale responses. 10 Facility recommendation score is an important complement to patient satisfaction indicators currently in use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to its relationship to visit quality, facility recommendation score might be less cognitively demanding for respondents and produces a continuous response that requires fewer assumptions in analysis than other measures, such as Likert scale responses. 10 Facility recommendation score is an important complement to patient satisfaction indicators currently in use.…”
Section: Discussionmentioning
confidence: 99%
“…To measure facility recommendation, we asked participants the following survey question: “Using a scale from zero to 10, where zero means you definitely would not recommend and 10 means you definitely would recommend, how likely is it that you would recommend this healthcare provider or facility to a friend or family member?” This item, a measure of potential future recommendation, has been used extensively in customer satisfaction surveys and has been proposed as a more intuitive indicator for evaluating health services. 10 The resulting recommendation score is the number between zero and ten selected by the respondent. Full survey questions and response options are available in appendix 2 (pp 1–2) .…”
Section: Outcome Definitionmentioning
confidence: 99%
“…This finding is consistent with two previous studies. In Peru, Leslie et al 20 found that user experience accounted for a larger proportion of variance in all user satisfaction measures, including three and five categories of net promoter score and satisfaction level, than the proportion explained by individual, facility and contextual factors combined. Similarly, Bleich et al ’s study 4 based on 21 European Union countries reported that all variables considered in the analyses (eg, user experience, user expectations) accounted for 17.5% of the observed variation in user satisfaction, of which 10% was explained by user experience.…”
Section: Discussionmentioning
confidence: 99%
“…We include both objective and subjective rankings to gauge what is acceptable to users in PLOS MEDICINE different contexts. We ask whether respondents would recommend the recently used facility to a friend or family member to calculate a net promoter score, an approach to assessing whether users are "promoters" or "detractors" of health care facilities [14].…”
Section: Plos Medicinementioning
confidence: 99%